Sediment redistribution due to a dense reservoir network in a largesemi-arid Brazilian basin - Lima Neto, Iran Eduardo (2011)
This paper investigates for a 25-year period the sediment distribution in a semi-arid Brazilian basin (2 × 104 km2 ) with a network containing more than 4000 surface reservoirs. The methodology is based on rating curves and fitted parameters derived from field data. The results showed that suspended load corresponded to 70% of the total sediment yield (148 t km-2 year -1 ). The relatively low contribution of the suspended load (compared with other semi-arid regions) was attributed to the impact of the numerous upstream reservoirs, which retained 235 t km-2 year -1 . The micro (<1 hm3 ), small (1–10 hm 3 ), medium-sized (10–50 hm 3 ), and large or strategic (>50 hm3 ) reservoirs responded to, respectively, 5, 17, 30 and 48% of the total sediment retention by the reservoir network. This indicates that retention in the non-strategic reservoirs has a positive impact on water availability, since siltation of the strategic reservoirs would be expected to more than double if only such reservoirs existed.